Effectiveness of Allium cepa L. Compress in Reducing Body Temperature Among Under-Five Children with Acute Respiratory Infections: A Quasi-Experimental Study - Zen, Dini Nurbaeti; Wibowo, Daniel Akbar; Ginanjar, Yoga (Journal of Applied Nursing and Health, 2026)
Background: Acute Respiratory Infections (ARI) are among the most common illnesses affecting children under five and are often accompanied by fever. Inadequately managed fever may lead to discomfort and potential complications. One complementary therapy widely used in communities is the application of shallot (Allium cepa L.) compresses. This study aimed to analyze the effectiveness of Allium cepa L. compresses in reducing body temperature among toddlers with ARI. Methods: A quasi-experimental design with a pretest–posttest control group approach was employed. The study involved 48 toddlers, divided into 24 intervention and 24 control groups, selected using purposive sampling. Body temperature was measured using a digital thermometer. Data were analyzed using Wilcoxon and Mann–Whitney tests. Results: The mean body temperature in the intervention group decreased from 38.2°C before intervention to 36.6°C after intervention, with an average reduction of 1.63°C. Statistical analysis showed a significant effect (p < 0.05). The control group experienced a smaller decrease (0.28°C). There was a significant difference between the intervention and control groups, with a large effect size (r = 0.87). Conclusion: Allium cepa L. compresses are effective in reducing body temperature among toddlers with ARI and can be considered a non-pharmacological intervention in pediatric nursing practice, particularly in primary healthcare settings.